Uji Aktivitas Antidiare Ekstrak Daun Mangkokan Terhadap Mencit yang Diinduksi Oleum Ricini - Stepfany Monica Helmin (Majalah Kedokteran Andalas, 2021)
Objective: the purpose of this study was to determine the antidiarrheal activity against mice induced by oleum ricini by giving various dose of mangkokan leaf extract; Method: this is an experimental research with post-test randomized control group design. This study used samples of male Balb/C mice weighing 20-35 grams which were acclimatized for a week before given any treatment. Mice were divided into 5 treatment groups: group A (given CMC 0.5% as negative control), group B (given loperamide as positive control), group C (given extract 150 mg/kgBW), group D (given extract 300 mg/kg), group E (given extract 600 mg/kgBW). Parameters observed were frequency of diarrhea, onset of diarrhea, duration of diarrhea, stool consistency, and stool weight; Result:  statistical test analysis showed significant results (P<0.05) on each observation parameter; Conclusion: Mangkokan leaf extract with a dose of 150 mg/kgBW, 300 mg/kgBW and 600 mg/kgBW has potential as antidiarrheal which shown in each parameter of observation. Dose that produced the best antidiarrheal activity was the mangkokan leaf extract at a dose of 600 mg/kgBW.